2019
DOI: 10.1016/j.rser.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Is the expansion of sugarcane over pasturelands a sustainable strategy for Brazil's bioenergy industry?

Abstract: Biofuels are fundamental for meeting societal energy needs within the next few decades, but the sustainability of large-scale land use conversions to supply feedstock crops remains unclear. Quantitative data documenting how biofuel crop expansion will affect ecosystem services (ES) is needed to develop sustainable energy policies. Using pairwise comparisons of published and novel environmental, social and economic indicators, we quantitatively assessed the provision of critical ES related to key aspects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 51 publications
2
27
0
9
Order By: Relevance
“…Our findings showing soil physical degradation and its consequent negative implications on water dynamics in extensive PA soils confirm what previous studies with a broader scope have reported, namely that those areas are characterized by poor overall soil quality [42] and provision of soil-related ecosystem services [13], low productivity and stocking rate [5], and low economic developments to farmers, workers, and the surrounding urban centers [13]. Due to all these environmental and socio-economic aspects, the prevalent scenario of sugarcane and other annual crops expansion has been, and will continue to be, over areas previously occupied with extensive pasture [4,13]. The full monitoring of PA soil conditions is fundamental to evaluate if sugarcane cultivation is degrading, sustaining, or even enhancing soil quality compared to the pasture baseline.…”
Section: Land Transition From Native Vegetation To Pasturesupporting
confidence: 91%
“…Our findings showing soil physical degradation and its consequent negative implications on water dynamics in extensive PA soils confirm what previous studies with a broader scope have reported, namely that those areas are characterized by poor overall soil quality [42] and provision of soil-related ecosystem services [13], low productivity and stocking rate [5], and low economic developments to farmers, workers, and the surrounding urban centers [13]. Due to all these environmental and socio-economic aspects, the prevalent scenario of sugarcane and other annual crops expansion has been, and will continue to be, over areas previously occupied with extensive pasture [4,13]. The full monitoring of PA soil conditions is fundamental to evaluate if sugarcane cultivation is degrading, sustaining, or even enhancing soil quality compared to the pasture baseline.…”
Section: Land Transition From Native Vegetation To Pasturesupporting
confidence: 91%
“…Brazil, one of the world's leading producers and suppliers of food, fibres and bioenergy 3 , is an emerging nation whose agriculture has rapidly expanded in recent decades, notably in the Cerrado region (over 204 million hectares (Mha)), and whose land base and deep soils provide large opportunity for conversion of extensive pasturelands into intensive croplands 4 . This land use transition is a promising scenario to allow agricultural expansion in Brazil with minimum environmental impacts 5 7 . However, one major economic and environmental issue associated with expansion and intensification of Brazilian agriculture is the substantial increase in fertiliser demand to sustain crop yields in these new areas (mainly in Cerrado region) characterized by highly-weathered, acid and P-fixing soils 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Other authors argue that ethanol has significantly grown in popularity due to government regulations and economic incentives [56], but that this kind of feedstock is essentially food, and other sources for bio-ethanol production exist that could substitute sugarcane [57]. At the same time, the demand for sugarcane used as biofuel in countries such as Brazil [58] has led to an increase in the sugarcane production area, in some cases, converting pasturelands to sugarcane fields [59]. This has been an important debate among researchers, generating many publications oriented towards the demonstration of its technical and economic viability for promising new raw materials, e.g., microalgae [60] or alternative energy sources, as well as the way to process them and the technology developed to that end, representing a threat for sugarcane based energy production.…”
Section: Discussionmentioning
confidence: 99%